Small RNA signatures of the anterior cruciate ligament from patients with knee joint osteoarthritis - Kharaz, Yalda A.; Zamboulis, Danae E.; Fang, Yongxiang; Welting, Tim J. M.; Peffers, Mandy J.; Comerford, Eithne J. (Frontiers in Molecular Biosciences, 2023)
Introduction: The anterior cruciate ligament (ACL) is susceptible to degeneration, resulting in joint pain, reduced mobility, and osteoarthritis development. There is currently a paucity of knowledge on how anterior cruciate ligament degeneration and disease leads to osteoarthritis. Small non-coding RNAs (sncRNAs), such as microRNAs and small nucleolar RNA (snoRNA), have diverse roles, including regulation of gene expression. Methods: We profiled the sncRNAs of diseased osteoarthritic ACLs to provide novel insights into osteoarthritis development. Small RNA sequencing from the ACLs of non- or end-stage human osteoarthritic knee joints was performed. Significantly differentially expressed sncRNAs were defined, and bioinformatics analysis was undertaken. Results and Discussion: A total of 184 sncRNAs were differentially expressed: 68 small nucleolar RNAs, 26 small nuclear RNAs (snRNAs), and 90 microRNAs. We identified both novel and recognized (miR-206, -365, and -29b and -29c) osteoarthritis-related microRNAs and other sncRNAs (including SNORD72, SNORD113, and SNORD114). Significant pathway enrichment of differentially expressed miRNAs includes differentiation of the muscle, inflammation, proliferation of chondrocytes, and fibrosis. Putative mRNAs of the microRNA target genes were associated with the canonical pathways “hepatic fibrosis signaling” and “osteoarthritis.” The establishing sncRNA signatures of ACL disease during osteoarthritis could serve as novel biomarkers and potential therapeutic targets in ACL degeneration and osteoarthritis development.